2010
DOI: 10.1128/aem.02268-09
|View full text |Cite
|
Sign up to set email alerts
|

Copper Stress Induces a Global Stress Response in Staphylococcus aureus and Represses sae and agr Expression and Biofilm Formation

Abstract: Copper is an important cofactor for many enzymes; however, high levels of copper are toxic. Therefore, bacteria must ensure there is sufficient copper for use as a cofactor but, more importantly, must limit free intracellular levels to prevent toxicity. In this study, we have used DNA microarray to identify Staphylococcus aureus copper-responsive genes. Transcriptional profiling of S. aureus SH1000 grown in excess copper identified a number of genes which fall into four groups, suggesting that S. aureus has fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
108
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(119 citation statements)
references
References 46 publications
10
108
1
Order By: Relevance
“…The copper-mediated repression of biofilm formation has been seen with other Gram-positive bacteria such as Staphylococcus aureus (74) and S. mutans (75). The addition of as little as 1 M copper is able to inhibit S. aureus biofilm formation (74). The authors of that study suggested that the effect was due to copper repression of the positive biofilm regulators Agr and Sae (74).…”
Section: Figmentioning
confidence: 82%
See 2 more Smart Citations
“…The copper-mediated repression of biofilm formation has been seen with other Gram-positive bacteria such as Staphylococcus aureus (74) and S. mutans (75). The addition of as little as 1 M copper is able to inhibit S. aureus biofilm formation (74). The authors of that study suggested that the effect was due to copper repression of the positive biofilm regulators Agr and Sae (74).…”
Section: Figmentioning
confidence: 82%
“…How do biofilms provide protection against copper-mediated killing of S. pyogenes? The copper-mediated repression of biofilm formation has been seen with other Gram-positive bacteria such as Staphylococcus aureus (74) and S. mutans (75). The addition of as little as 1 M copper is able to inhibit S. aureus biofilm formation (74).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings suggest that alterations in sulfur metabolism influence the ability of Sau to form biofilms, an essential feature of its ability to thrive both inside and outside of the host (32). Microarray experiments carried out on mid-log liquid cultures of S. aureus SH1000 reveal that copper stress, sufficient to induce the CsoR-dependent expression of copA and perhaps other genes that function in oxidative stress resistance (25), negatively regulates biofilm formation via repression of the sae and agr regulons (52). Thus, CsoR and CstR-related stress response pathways may be physiologically linked by a connection to alteration in biofilm formation and oxidative stress and ultimately viability in the vertebrate host.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the gene encoding the likely copper chaperone CopZ just downstream from copA (Fig. 1A) is induced by copper (24,25), but may not be co-transcribed with copA (24). Although it is not yet known whether the transcription of copZ is also regulated by CsoR, inspection of the intergenic region between copA and copZ does not reveal an obvious candidate CsoR binding site like that found in the copA operator-promoter region, nor have we determined if copZ transcription is altered in the ⌬csoR strain.…”
Section: Discussionmentioning
confidence: 99%